Effectiveness of the Use Hospital Information And Management System (SIMRS) For Services Based on Hot-Fit Theory - Nugroho, Tri Adi; Mufreni, Agung; Wulandari, Rizki Yeni; Wijayanto, Wisnu Probo (Universitas Aisyah Pringsewu, 2022)
The use of a computer-based Hospital Information and Management System (SIMRS) in the Medical Record unit is carried out in an integrated manner. The data management process includes, among others, data collection (registration), data processing (assembling, coding, indexing), and data reporting. The SIMRS implementation at the general hospital of Az-Zahra has not yet been fully implemented. The objective of this study was to determine the effectiveness of the use of hospital information and management systems (SIMRS) for services at the general hospital of Az-Zahra Kalirejo through the HOT-FIT theory. This type of research was qualitative, the research design used exploratory with the objective of describing the effectiveness of the use of Hospital Information and Management systems for services at the general hospital of Az-Zahra Kalirejo. The population in this study was 134 people, and the sample in this study was 9 informants, namely the doctor in charge of services (DPJP), general practitioner and head of finance. The results of the study are known in the human aspect, SIMRS officers at the general hospital of Az-Zahra already understand how to use SIMRS, but for specialist doctors and general practitioners they are still assisted by nurses in inputting. In the organizational aspect, it is known that the directors, management and staff of the hospital fully support the use of SIMRS. The technology aspect of SIMRS at the general hospital of Az-Zahra is in accordance with the accreditation standards of the Hospital and Social Security Administrator’s Health, but often experiences problems with the internet network, which can interfere with the operation of using SIMRS. Researchers suggest that SIMRS training be held for general practitioners and specialists, as well as improving the internet network so that the connection is even better.